2013
DOI: 10.1021/cb4000234
|View full text |Cite
|
Sign up to set email alerts
|

Eupalinilide E Inhibits Erythropoiesis and Promotes the Expansion of Hematopoietic Progenitor Cells

Abstract: Hematopoietic stem cells (HSCs) are the progenitor cells that give rise to all blood cells. The ability to control HSC differentiation has the potential to improve the success of bone marrow transplants and the production of functional blood cells ex vivo. Here we performed an unbiased screen using primary human CD34(+) hematopoietic stem and progenitor cells (HSPCs) to identify natural products that selectively control their differentiation. We identified a plant-derived natural product, eupalinilide E, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…A total of 13 different cell lines originated from humans, mice, and rats were evaluated in the studies ( Figure 3 ). Among them, four cells were cancer cell lines including, mice melanoma B16 cells ( Ye et al, 2011 ), human HL-60 cell line ( Choi et al, 2002 ; Kim et al, 2005 ; Kim et al, 2006 ; Kweon et al, 2015 ), human CML cell line K562 ( Huang et al, 2016 ; Cai et al, 2017 ), human AML cell line U937 ( Huang et al, 2016 ), three cells were stem cells including rat mesenchymal stem cell ( Li et al, 2012 ), mice mesenchymal stem cells C3H10T1/2 ( Kim et al, 2017 ), hematopoietic stem and progenitor cells (HSPCs) ( de Lichtervelde et al, 2013 ), and six cells were normal cell lines including, 3T3-L1 cell line ( Galvis et al, 2011 ; Jang, 2016 ; Kim et al, 2016 ; Abood et al, 2018 ; Kwak and Kim, 2019 ), mice bone marrow macrophage ( Cheon et al, 2014 ; Hu et al, 2019 ; Lee et al, 2019 ; Li et al, 2019 ; Zhou et al, 2019 ; Lu et al, 2020 ), CD4 + T cell ( Park et al, 2016 ), human periosteum-derived cells ( Park et al, 2020 ), human preadipocytes ( Jang, 2016 ), mice MC3T3-E1 cell line ( Kim et al, 2017 ). All cell lines except the murine melanoma B16 cell line had a mesodermal origin.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 different cell lines originated from humans, mice, and rats were evaluated in the studies ( Figure 3 ). Among them, four cells were cancer cell lines including, mice melanoma B16 cells ( Ye et al, 2011 ), human HL-60 cell line ( Choi et al, 2002 ; Kim et al, 2005 ; Kim et al, 2006 ; Kweon et al, 2015 ), human CML cell line K562 ( Huang et al, 2016 ; Cai et al, 2017 ), human AML cell line U937 ( Huang et al, 2016 ), three cells were stem cells including rat mesenchymal stem cell ( Li et al, 2012 ), mice mesenchymal stem cells C3H10T1/2 ( Kim et al, 2017 ), hematopoietic stem and progenitor cells (HSPCs) ( de Lichtervelde et al, 2013 ), and six cells were normal cell lines including, 3T3-L1 cell line ( Galvis et al, 2011 ; Jang, 2016 ; Kim et al, 2016 ; Abood et al, 2018 ; Kwak and Kim, 2019 ), mice bone marrow macrophage ( Cheon et al, 2014 ; Hu et al, 2019 ; Lee et al, 2019 ; Li et al, 2019 ; Zhou et al, 2019 ; Lu et al, 2020 ), CD4 + T cell ( Park et al, 2016 ), human periosteum-derived cells ( Park et al, 2020 ), human preadipocytes ( Jang, 2016 ), mice MC3T3-E1 cell line ( Kim et al, 2017 ). All cell lines except the murine melanoma B16 cell line had a mesodermal origin.…”
Section: Resultsmentioning
confidence: 99%
“…The aqueous mixture was extracted with Et 2 O (3 × 100 mL), and the combined organic layers were washed with brine (1 × 50 mL), dried over Na 2 SO 4 , and concentrated in vacuo. The crude material was purified via silica gel column chromatography using 10/1 hexanes/ EtOAc to give the triene 24 (2.19 g, 6.22 mmol, 37%) as a yellow oil: R f = 0.5 (silica gel, 10/1 hexanes/EtOAc); 1 ((2S,3S)-2-((1R,4R,5R)-4-((4-Methoxybenzyl)oxy)-2-methyl-5-(prop-1-en-2-yl)cyclopent-2-en-1-yl)-4-methylenetetrahydrofuran-3-yl)methanol (26). To a stirred solution of triene 24 (1.36 g, 3.86 mmol, 1.0 equiv) in PhMe (38.6 mL, 0.1 M) at 23 °C were added solid bis(pinacolato)diboron (1.08 g, 4.24 mmol, 1.1 equiv), solid palladium(II) acetate (43 mg, 0.19 mmol, 0.05 equiv), and neat MeOH (0.16 mL, 72.1 mmol, 1.0 equiv).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…From a relatively small library of natural products of variable origin (∼700 compounds), eupalinilide E was shown to markedly drive the expansion of HSPCs and inhibit differentiation, leading to a large increase in the number of HSPCs. 26 This effect was possible using either cord blood or human mobilized peripheral blood. Remarkably, this proliferative effect was demonstrated at 600 nM, approximately 20-fold of the concentration used previously to kill A549 lung cancer cells.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Lichtervelde et al [24] have identified a new pharmacological agent, Eupalinilide E that inhibits erythropoiesis and promotes the expansion of hematopoietic progenitor cells. The activity of Eupalinilide E, a natural product, was found to have additive effects with AhR antagonists.…”
Section: Chemical Compounds (Small Molecules)mentioning
confidence: 99%